Splenic Artery Pseudoaneurysm Masquerading as a Pancreatic Cyst—A Diagnostic Challenge - Chia, C. (Int Surg, 2015)
Splenic artery pseudoaneurysm is a rare entity. Clinical diagnosis is challenging because presentation is often varied. It can range from an incidental finding to hemodynamic collapse from sudden rupture and bleeding. The most common cause of this condition is pancreatitis. We report an unusual case of a young man not known to have pancreatitis who presented with hematemesis with normal esophagogastroduodenoscopy. Imaging modalities did not lead to a definitive diagnosis, and he underwent emergency laparotomy with surgical ligation of splenic artery pseudoaneurysm for hemodynamic instability, without a definitive preoperative diagnosis.